Implementation of Benchmarking Method for Higher Education Institution: A Literature Review - Bayu Hari Nugroho; Choesnul Jaqin (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
Benchmarking is a systematic and continuous process by comparing the products, processes, and results of an organization with other similar organizations. Benchmarking is generally done by comparing it to an organization that has a better level because it aims to provide input for internal improvement in the organization so that it becomes better than the position before the benchmarking was done. Educational institutions also need to carry out a benchmarking process as this can contribute to determining learning and promotion strategies, improving the learning process and curriculum development, improving physical infrastructure facilities, improving operations, performance. In this study, the method used is a literature review of 35 journals, then the classification is done based on the country and the type of benchmark performed. The results show that until 2020 the benchmarking process is still being carried out and continues to be carried out in various countries, both in developed countries to developing countries. However, from the literature that has been reviewed, there are still gaps to examine the strengths and weaknesses of higher education in terms of implementing the digitalization of educational systems, the quality of graduates with a digital education system, and implementing digital libraries in universities. Types of benchmarking processes and benchmarking strategies can be carried out to research the implementation of digital education, this is because it is a type of benchmarking process and strategy that can determine global competition.